Malaysian perceptions on Rayani Air’s Islamic corporate image and its impact on the future Islamic Airlines / Nadia Mohd Nazri...[et al.] - Mohd Nazri, Nadia; Adzharuddin, Nor Azura; Ridzuan, Abdul Rauf (Universiti Teknologi MARA, Kedah, 2020)
Rayani Air’s establishment as the fourth Islamic airline in world and the first Islamic carrier received spectrum attention from the top to bottom line of public in Malaysia and worldwide. However, Rayani Air failed to maintain its good publicity and the consistency of a good Islamic corporate image. Their reputation declined as they failed to solve several issues and crises that occurred which led to its shutdown. The researcher conducted the interview sessions with the company founder, ex-customers of Rayani Air, the aviation and ‘shariah’ experts and did content analysis to explore the corporate issue of Rayani Air. Objective: The findings of this study will embark the new guideline of the real practice of Islamic corporate image in any airline corporations based on the notions and needs of public in Malaysia. Knowing the market Islamic identity or label that layered behind the organisations’ image is vital necessity for the need of Muslim consumers around the world. Results:Majority of the public changed their positive perceptions negatively after the shutdown of Rayani Air. Their perceptions of Rayani Air’s corporate image are moderately satisfied. Most of the informants admitted that they were keen on its Islamic identity and trigger their attention to try out the service but what made most of them bought the ticket were because of its affordable ticket fare, cheap but high-quality service provided at the beginning of the company’s kick-start. Their biggest disappointments were the failure of the company to fulfil the promises of good ‘shariah’ services to the customers. Conclusion: It is crucial for the Islam based business entrepreneurs to learn the facts and give their utmost respect towards the religion while making profit for both owners’ and costumers’ benefits which uplifting the name of Islam itself world widely. Aviation industry is a dog-eat-dog deal. One cannot simply manipulate the holiness of Islam for the sake of self-profit in the business. Right image with wrong intention will dim the white and light of Islam among the public.